2022
DOI: 10.1101/2022.03.14.22272359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomarkers Selection for Population Normalization in SARS-CoV-2 Wastewater-based Epidemiology

Abstract: Wastewater-based epidemiology (WBE) has been one of the most cost-effective approaches to track the SARS-CoV-2 levels in the communities since the COVID-19 outbreak in 2020. Normalizing SARS-CoV-2 concentrations by the population biomarkers in wastewater can be critical for interpreting the viral loads, comparing the epidemiological trends among the sewersheds, and identifying the vulnerable communities. In this study, five population biomarkers, pepper mild mottle virus (pMMoV), creatinine (CRE), 5-hydroxyind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…In addition, our previous study confirmed that direct normalization effects of SARS-CoV-2 concentration using biomarker concentrations were always less ideal than indirect normalization, which involved the wastewater volume. 29…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, our previous study confirmed that direct normalization effects of SARS-CoV-2 concentration using biomarker concentrations were always less ideal than indirect normalization, which involved the wastewater volume. 29…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous study confirmed that direct normalization effects of SARS-CoV-2 concentration using biomarker concentrations were always less ideal than indirect normalization, which involved the wastewater volume. 29 Our findings suggest that for long-term wastewater SARS-CoV-2 surveillance, normalizing SARS-CoV-2 wastewater concentrations with a reliable population marker prior to calculating trends is highly recommended to account for changes in wastewater dilution and differences in relative human waste input over time due to tourism, weekday commuters, temporary workers, and pandemic lockdowns, etc. This approach is particularly critical for the sewershed with dynamic population changes, such as colleges, tourist towns, and metropolitan areas, where a large number of commuters who used to travel to cities daily transitioned to fully or partially remote workers after the pandemic.…”
Section: Normalization Approach Recommendation For Sars-cov-2 Wastewa...mentioning
confidence: 90%
See 3 more Smart Citations